Relações da informação com os pequenos negócios, a partir do balcão: além da rima - há solução - Raimundo Nonato Uchoa Araujo (2001)
This study investigates the informational basis provided by Balcão do SEBRAE-PI, with which the micro and small entrepreneurs install, amplify and modernize their business. By means of a direct research it was possible to delineate the profile of entrepreneurs who ask for information at Balcão SEBRAE-PI, what kind of information and resources they consider of great relevance as well as their reasons to enter in the business world. It was also investigated the moment when, in fact, they register their enterprises at the competent institution - in this case, Secretaria da Fazenda do Estado do Piauí. According to the premise that information, as presented in business literature, is the main input to creation and maintenance of enterprises, especially considering the present social, economic and political context in the Brazil, this study demonstrates that the lack or inadequate use of information may determine premature bankruptcy. In generic terms, it can be concluded that there are faults both in the provision of information and in its use. Some suggestions are presented in order to contribute to the performance of institutions that failures support micro and small entrepreneurs.